Ability to Understand Mathematical Concepts in Elementary Schools: Systematic Literature Review and Bibliometric Analysis - Wardani, Ranti Kusuma Wardani; Darmayanti, Mela Darmayanti (Jurnal Pendidikan dan Kebudayaan Missio, 2024)
The research aims to determine research developments related to the ability to understand elementary school students' mathematical concepts for the 2013–2023 period. It is hoped that these findings will become a reference for further research. This research uses a systematic review and bibliometric analysis. The research uses an application to obtain results and articles from the Google Scholar database which are collected using Publish or Perish (PoP) software and visualized with the help of the Vosviewer software application. The findings show that in understanding mathematical concepts in elementary schools what is widely discussed is related to media and learning models that can be used to improve students' understanding of mathematical concepts, such as the AIR model, RME model, TGT model, PAIKEM model, STAD type model, based learning model. problems, explicit learning models, problem solving, and problem posing models, as well as dakon media and scale units, cube tool unit media, classroom screen media and Google Jamboard, video-based contextual learning media, counting funnel media, sempoa media, and drinking straws and number bag. The research subjects were dominated by fifth and fourth grade students who were mostly researched, and the understanding of the most widely studied mathematical concepts was related to geometry.